Attitudes of the Portuguese farmers to the EU common agricultural policy = Postoje portugalských farmá?? ke spole?né zem?d?lské politice EU - Dos-Santos, M.; de Sousa Henriques, P. D.; de Sousa Fragoso, R. M.; da Silva Carvalho, M. L. P. V. (Agricultural Economics (AGRICECON), 2010)
The main purpose of this paper aims to know the farmer's attitudes towards the agricultural production, the political support, and the irrigation project of Alqueva in the context of the 2003 Ccommon Agricultural Policy (CAP) Rreform, the Health-Check, in a micro-region located near the Mediterranean Sea. For this purpose, we use the Theory of Planned Behaviour. The main results suggest that the majority of farmers are a relatively homogeneous cluster about their attitudes but not in their behavioural intentions. These farmers still maintain a productivist mindset, wish to maintain an agricultural focus and strongly reject the notions of policy liberalisation. The main conclusions suggest that although the farmers have a great potential of innovating the future CcAP policies, the water supply irrigation price and the conditions of access to agricultural credit, may compromise their innovation capacity in the future, in particular on the smaller farms.